Rancangan Blended Learning Matematika Bagi Pendidikan Vokasional Masa Pandemi Covid-19 - Darma I Ketut; Karma I Gede Made; Anom Santiana I Made (Jurnal Pembelajaran dan Pengembangan Matematika, 2022)
The era of the industrial revolution 4.0 and the Covid-19 pandemic requires an educator to innovate in packaging the learning process to be more efficient and interesting. Mathematics learning in vocational education is required to be student-centered and emphasizes aspects of creativity and innovation, critical thinking and problem solving, communication and collaboration. Blended learning, an innovative learning that combines online learning with face-to-face, has three components, namely online learning, face-to-face learning, and independent learning. This research is a qualitative research in the nature of a literature study, aiming to obtain a mathematical blended learning design model for vocational education during the Covid 19 pandemic. The data are sourced from various books, journals, proceedings related to blended learning, vocational education and covid 19. The results of the analysis show that blended learning mathematics is designed for 2 Semester credit units using the flipped learning model and the LMS application of schoology applications based on the learning theories of Behaviorism, Cognitivism, Constructivism, Connectivism, and Cybernitism. The components include: 1) learning outcomes, 2) material organization maps, 3) reference lists, 4) teaching materials/materials, 5) synchronous and asynchronous learning activities, asynchronous learning designs, 6) synchronous learning designs, 7) learning designs. synchronous, and 8) synchronous learning flow. The implication is that this design can be an effective solution for learning mathematics in the IR era. 4.0 and the Covid-19 pandemic on vacational education.